FAKTOR PENENTU BIAYA KEAGENAN: STUDI EMPIRIK PADA EMITEN PEMBENTUK INDEKS LQ45 - Bram Hadianto; Herlina . (Journal of Management and Business, 2011)
The purpose of this research is to know the impact of debt policy, dividend policy, board commissioner size, and institutional ownership on agency cost. Following Ang et al. (2000), asset utilization ratio (AUR) and operating expense ratio (OER) used as measurement of the agency cost. LQ45 index constituent firms are used as the sample which determined by the purposive sampling technique. The regression model with polled data conducted as data analysis method. The results show that institutional ownership is the only factor that has impact on agency cost measured by asset utilization ratio with positive sign.